Pengembangan Model Sistem Dinamis Suppy Chain di PT XYZ - Muhammad Dwiyanto Saputro; Maulida Boru Butar Butar (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
PT.XYZ is an automotive company that has been operational since 1970, with over 400 suppliers for key components such as Stoper A and Stoper B. Annually, Stoper A sells 151,000 units (valued at IDR 4.077 billion), while Stoper B reaches 300,000 units (valued at IDR 8.100 billion). This research focuses on analyzing and optimizing the supply chain for these components, using sales data from January to December 2022. The goal is to create stock and flow diagrams, analyze the supply chain system modeling, and propose optimal scenarios for demand fulfillment. The modeling results indicate that a strategy of adding a 20% safety stock to the average sales is highly effective in preventing lost sales without burdening suppliers with overtime. However, the potential for overstock needs to be monitored. Based on the analysis, the second scenario proposing the addition of safety stock is recommended due to its effectiveness in meeting demand and efficiently managing inventory. This scenario is deemed most suitable for PT. XYZ in maintaining a balanced supply without unnecessary surplus.